Ang Kababaihan at Nasyonalismo sa Kasaysayan - Estrada-Claudio, Sylvia (Review of Women's Studies, 2023)
This paper looks at the contradictory relationship of feminism and nationalism. While one common trope in feminist historiography is to surface the role of women in Philippine history, it argues that there is a need to understand that the concept of the nation and nationalism are social constructs with their own histories. It argues further that a more grounded and detailed analysis is necessary in order to understand the nuanced and often contradictory relationship of the ideologies of nationalism and feminism. The paper suggests that such a critical interrogation opens up new analytical and research possibilities for engaged scholars and other social actors.